Personalidade de pais e mães envolvidos em casos de alienação parental - Jacobi, Michéli da Silva (2019)
The theme of parental alienation is often related to marital separation and to family relationships between parents and children in which a parent, by means of abusive acts, defames, disqualifies the other parent and manipulates the child agains the other parent. This study had the objective of investigating the personality of parents involved in cases of parental alienation (possibly alienating and alienated). The sample was made of 17 parents, divided in two groups regardless of gender. The alienating suspects formed the G1 (n=09), age group: 23 – 58 years old (AM= 39,5 and SD= 7,87), while the alienated suspects formed the G2 (N=08), age group: 25 – 53 years old (AM= 40,0 and SD= 9,44). For both groups, the sample was made of parents involved in mediation or in legal proceedings on Mato Grosso Court of Justice (TJMT), in which were accused or were accusing the other parent of parental alienation, and that were participants of the “Parents and Children” Workshop of the Permanent Center of Mediation Methods (Núcleo Permanente de Métodos Consensuais de Solução de Conflitos – NUPEMEC). As instruments in this study, it was useda semi-directed interview (elaborated by the author), a social demographic questionnaire and the Rorschach Test following the R-PAS and the Parental Alienation Scale (EAP). As a result, the majority of the accusations of parental alienation are against women. On the EAP, there were significant statistical differences between the two groups and in the total, on the categories of preventing/difficulting and defame/disqualify. In the Rorschach Test, alienating and alienated suspects presented similarities in indicators of disturbance of thought, distorted judgment and reality perception and difficulty in relationships, and reveled that there are diferences between the two groups. The alienating suspects presented indicators of narcissistic traits, egocentrism and individualistic tendencies. We highlight that the alienating behavior are related to the psychic functioning of parents in the context of separation, and not exclusively in a legal proceeding. We concluded that people involved in this type of situation of judicial conflict are more predisposed to dysfunctional behavior, disorganization of thought, with propensity to see the obvious and conventional things of reality in a very personal and misguided way, and also present difficulties in relationships. From this findings, we highlight that the Rorschach Test can contribute in the personality evaluation of people involved in cases of parental alienation.